Advancing therapy in people with suboptimally controlled basal insulin-treated type 2 diabetes: Subanalysis of the SoliMix trial in participants in Latin American countries - Frechtel, Gustavo Daniel (2023)
Aims: This subanalysis of the SoliMix trial assessed the efficacy and safety of advancing basal insulin (BI) therapy with iGlarLixi versus BIAsp 30 in people with type 2 diabetes (T2D) living in Latin American (LATAM) countries, i.e. Argentina and Mexico (N = 160). Materials and Methods: SoliMix (EudraCT: 2017-003370-13) was a 26-week, open-label, multicentre study, where adults with T2D suboptimally controlled with BI plus one or two oral glucose-lowering drugs and glycated haemoglobin (HbA1c) ≥7.5% to ≤10% were randomized to once-daily iGlarLixi or twice-daily BIAsp 30. Primary efficacy endpoints were non-inferiority in HbA1c reduction (margin 0.3%) or superiority in body weight change for iGlarLixi versus BIAsp 30. Results: Both primary efficacy endpoints were met in the LATAM region. After 26 weeks, HbA1c was reduced by 1.8% with iGlarLixi and 1.4% with BIAsp 30, meeting non-inferiority [least squares mean difference −0.47% (95% confidence interval: −0.82, −0.11); p <.001]. iGlarLixi was superior to BIAsp 30 for body weight change [least squares mean difference −1.27% (95% confidence interval: −2.41, −0.14); p =.028]. iGlarLixi was also superior to BIAsp 30 for HbA1c reduction (p =.010). A greater proportion of participants achieved HbA1c <7% without weight gain and HbA1c <7% without weight gain and without hypoglycaemia with iGlarLixi versus BIAsp 30. Incidence and rates of American Diabetes Association Level 1 and 2 hypoglycaemia were lower with iGlarLixi versus BIAsp 30. Conclusions: Once-daily iGlarLixi provided better glycaemic control with weight benefit and less hypoglycaemia than twice-daily premix BIAsp 30. iGlarLixi may be a favourable alternative to premix BIAsp 30 in people with suboptimally controlled T2D to advance BI therapy in the LATAM region.